Functional Integration Between the Two Brain Hemispheres: Evidence From the Homotopic Functional Connectivity Under Resting State - Jin, Xinhu; Liang, Xinyu; Gong, Gaolang (Frontiers in Neuroscience, 2020)
Functional integration among neural units is one of the fundamental principles in brain organization that can be examined using resting-state functional connectivity (rs-FC). From a left- and right-hemisphere perspective, previous studies have reported that interhemispheric functional integration plays a critical role in cognition. Homotopic functional connectivity (HoFC) under resting state can allow the direct investigation of functional integration between the two brain hemispheres and improve the present understanding of how interhemispheric interactions affect cognitive processing. In this review, we summarize the progress of HoFC studies performed with resting-state functional magnetic resonance imaging (rs-fMRI) and emphasize how these findings have enhanced our understanding of hemispheric functional organization in the human brain. Future approaches are encouraged to address particular methodological issues and to further identify the behavioral correlation, disease's modulation, task influence and genetic basis of HoFC.